Pengaruh Substitusi Tepung Sorgum TanpaSosoh Terhadap Warna Dan Daya Patah Biskuit - Annisa Alfiana, Trias, Eni Purwani, S.Si., M.Si, Rusdin Rauf, S.TP., M.P (2017)
Introduction: Whole sorghum flour potentially be used as flour for biscuits processed into a much-loved by the people. Determinants of quality biscuits namely chemical properties, sensory, and physical properties. Broken power and the color is part of the physical properties of biscuits. Objective: The aim of research to find out how the effect of substitution of whole sorghum flour of color and broken biscuits. Methods: The completely randomized design with four substitutions in whole sorghum flour 0%, 15%, 30%, and 45%. Color and fracturability analyzed by ttest and One Way Anova. Result: The results showed that the color of the biscuits by 0%, 15%, 30% and 45% had a value of p <0.05. Therefore, no different then tested Duncan, Duncan test results showed no difference between the color value whole sorghum flour substitution on sorghum biscuits.The influence of fracturability biscuits from whole sorghum flour substitution the average value p≥0,05 which means fourth treatment has no significant difference in fracturability biscuits. Conclusion: There is the effect of various concentrations on biscuits substituted whole sorghum flourto biscuit color sorghum. There is no influence of various concentrations on biscuits substituted whole sorghum flour to fracturability the biscuit sorghum. Suggestion: Need further research on the application whole sorghum biscuits for diabetics to replace refined sugar with low calorie sugar. Consumers are advised to consume whole sorghum biscuit with the substitution of 45% because of the high fiber content and good for digestion.